Побудова інтелектуальних систем безпеки на базі ESP32-Cam - Легезін, К. О. (ХНУРЕ, 2025)
The work shows the need to recognize different classes of moving objects in security systems. The hardware capabilities of ESP32-Cam modules for embedding image recognition algorithms in the video stream from the camera are analyzed. The TensorFlow Lite neural network has been implemented in the ESP32-Cam for recognizing people.
Keywords: ESP32-Cam; побудова систем безпеки